Acute exacerbation of unclassifiable idiopathic interstitial pneumonia: comparison with idiopathic pulmonary fibrosis. (June 2020) - Enomoto, Noriyuki; Naoi, Hyogo; Aono, Yuya; Katsumata, Mineo; Horiike, Yasuoki; Yasui, Hideki; Karayama, Masato; Hozumi, Hironao; Suzuki, Yuzo; Furuhashi, Kazuki; Fujisawa, Tomoyuki; Inui, Naoki; et al.
Background: Acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF) is well known as a life-threatening condition during its clinical course. However, the clinical features and prognosis in AE of unclassifiable idiopathic interstitial pneumonia (AE-UCIIP) remain to be elucidated. The aim of this study was to clarify the clinical features and prognosis of AE-UCIIP compared with those of AE-IPF. Methods: In 187 patients with UCIIP or IPF, 64 patients with AE-UCIIP or AE-IPF, who were diagnosed and treated at our hospital, were retrospectively evaluated. Results: A total of 24 patients with AE-UCIIP were significantly older ( p  = 0.011), included more women ( p  < 0.001) and never-smokers ( p  < 0.001), and showed fewer lung lesions on high-resolution computed tomography ( p  = 0.006) than 40 patients with AE-IPF. Incidence of AE-UCIIP was 10.29%/year and was significantly higher than in AE-IPF (Gray's test, p  = 0.008). Prognosis of AE-UCIIP was as poor as that of AE-IPF (log-rank, p  = 0.681). Percent-predicted forced vital capacity (%FVC) [hazard ratio (HR) 0.934, p  = 0.045], and GAP stage within 12 months before AE (HR 3.530, p  = 0.023), and partial pressure arterial oxygen/fraction of inspired oxygen (PaO2 /FiO2 ) ratio at AE (HR 0.998, p  = 0.016) were significant prognostic factors. Finally, commencement of long-duration (⩾12 h) direct hemoperfusion with a polymyxin B-immobilised fibre column (PMX-DHP) within 2 days after admission significantly improved survival (log-rank, p  = 0.038) and was a significant prognostic factor (HR 0.175, p  = 0.0039) in AE-UCIIP. Long-duration PMX-DHP showed favourable treatment effects even in the combined group of patients with AE-UCIIP or AE-IPF (log-rank p  = 0.002; HR 0.328, p  = 0.006). Conclusions: Patients with AE-UCIIP were older and included more women and never-smokers than those with AE-IPF. Prognosis of AE-UCIIP was as poor as that of AE-IPF. The reviews of this paper are available via the supplemental material section.